The relationship between quantitative magnetic resonance imaging of the ankle plantar flexors, muscle function during walking and maximal strength in people with neuromuscular diseases. (April 2022) - Waterval, N.F.J.; Meekes, V.L.; Hooijmans, M.T.; Froeling, M.; Jaspers, R.T.; Oudeman, J.; Nederveen, A.J.; Brehm, M.A.; Nollet, F.
Abstract: Background: Progression of plantar flexor weakness in neuromuscular diseases is usually monitored by muscle strength measurements, although they poorly relate to muscle function during walking. Pathophysiological changes such as intramuscular adipose tissue affect dynamic muscle function independent from isometric strength. Diffusion tensor imaging and T2 imaging are quantitative MRI measures reflecting muscular pathophysiological changes, and are therefore potential biomarkers to monitor plantar flexor functioning during walking in people with neuromuscular diseases. Methods: In fourteen individuals with plantar flexor weakness diffusion tensor imaging and T2 scans of the plantar flexors were obtained, and the diffusion indices fractional anisotropy and mean diffusivity calculated. With a dynamometer, maximal isometric plantar flexor strength was measured. 3D gait analysis was used to assess maximal ankle moment and power during walking. Findings: Fractional anisotropy, mean diffusivity and T2 relaxation time all moderately correlated with maximal plantar flexor strength ( r  > 0.512). Fractional anisotropy and mean diffusivity were not related with ankle moment or power ( r  < 0.288). T2 relaxation time was strongly related to ankle moment ( r  = −0.789) and ankle power ( r  = −0.798), and moderately related to maximal plantar flexor strength ( r  < 0.600). Interpretation: In conclusion, T2 relaxation time, indicative of multiple pathophysiological changes, was strongly related to plantar flexor function during walking, while fractional anisotropy and mean diffusivity, indicative of fiber size, only related to maximal plantar flexor strength. This indicates that these measures may be suitable to monitor muscle function and gain insights into the pathophysiological changes underlying a poor plantar flexor functioning during gait in people with neuromuscular diseases. Highlights: Quantitative imaging of the plantar flexors was collected in neuromuscular diseases. Diffusion Tensor Imaging parameters related with maximal isometric strength. Quantitative T2 imaging strongly related with maximal ankle moment and power. Outcomes provide insights into pathophysiological changes causing gait changes. Quantitative imaging may be used to monitor muscle function deterioration.